1977
DOI: 10.1080/00378941.1977.10835756
|View full text |Cite
|
Sign up to set email alerts
|

Analyse du port chez desPetunia

Abstract: Summaru. -Habit of twelve )ines of Pt•funia hubrida and threc lincs of Petunia axiflaris, uiolaeea and parodii : the gcnetie differ·cm·es bctwccn lhcsc !ines t!o appcar in the expression of this trait, sorne charactcristil·s of which vary in relation to the endronmental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…This observation is not unexpected, since it is known that leaf parameters in Petunia are significantly influenced by environmental conditions such as temperature, light intensity and duration, and nutrient levels. For example, Brunard et al (1977) observed similar environmental influences on the habit of Petunia in a comparative study of the same species examined herein. Likewise, vegetative plant data enumerated during different seasons in an earlier study (Sink et a l .…”
Section: Resultssupporting
confidence: 53%
“…This observation is not unexpected, since it is known that leaf parameters in Petunia are significantly influenced by environmental conditions such as temperature, light intensity and duration, and nutrient levels. For example, Brunard et al (1977) observed similar environmental influences on the habit of Petunia in a comparative study of the same species examined herein. Likewise, vegetative plant data enumerated during different seasons in an earlier study (Sink et a l .…”
Section: Resultssupporting
confidence: 53%
“…For many species, differences occur in growth habit between cultivars. In different petunia cultivars, the number of nodes that produce branches can vary, as well as the positioning of the basal branches along the shoot axis (Brunaud et al, 1977 ; Drummond et al, 2009b ).…”
Section: Introductionmentioning
confidence: 99%